1999
DOI: 10.1164/ajrccm.159.2.9804080
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Permeability, Inflammation, and Oxidant Stress in the Air Spaces of Smokers

Abstract: The mechanism responsible for the increased air-space permeability in cigarette smokers is unknown. The aim of this study was to assess the acute and chronic effects of cigarette smoking on epithelial permeability, inflammation, and oxidant stress in the air spaces of smokers. Fourteen cigarette smokers underwent 99mTc-diethylenetriamine pentaacetic acid (99mTc-DTPA) lung scans after abstaining from smoking for 12 h (chronic smoking) and 1 h after smoking two cigarettes (acute smoking). Each smoker also underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
171
1
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(194 citation statements)
references
References 31 publications
15
171
1
7
Order By: Relevance
“…We, and others, have shown that leukocytes isolated from patients with COPD release high levels of O 2 ⅐ , 15,16 which was associated with increased systemic levels of inflammatory mediators. 17,18 Hence, inhibition of CS-induced generation of ROS would confer protection against oxidantmediated lung inflammation.…”
Section: Cigarette Smoke (Cs) Induces Recruitment Of Inflammatory Celmentioning
confidence: 79%
See 2 more Smart Citations
“…We, and others, have shown that leukocytes isolated from patients with COPD release high levels of O 2 ⅐ , 15,16 which was associated with increased systemic levels of inflammatory mediators. 17,18 Hence, inhibition of CS-induced generation of ROS would confer protection against oxidantmediated lung inflammation.…”
Section: Cigarette Smoke (Cs) Induces Recruitment Of Inflammatory Celmentioning
confidence: 79%
“…19 -22,50,51 We, and others, have shown that O 2 ⅐Ϫ release is increased from leukocytes isolated from smokers and in patients with COPD, 15,16 as well as from endothelial cells in response to CS that is mediated via NADPH oxidase activation. 11,12 However, the role of NADPH oxidase in CS-induced lung inflammation is not known.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…42 Human studies have shown elevated levels of GSH in epithelial lining fluid in chronic cigarette smokers compared to non-smokers. 42,43 Enzymatic antioxidant defences include SOD, catalase, thioredoxin, Gpx, and glutathione-S-transferase. Bronchial epithelial cells of rats exposed to cigarette smoke have shown increased expression of the antioxidant genes manganese superoxide dismutase, metallothionein, and Gpx.…”
Section: Endogenous Antioxidant Defences Within the Lungmentioning
confidence: 99%
“…The increased synthesis of nitric oxide may be caused by activation of inducible NO-synthase which is expressed in macrophages, neutrophils, mast cells, endothelial, epithelial cells and smooth muscle cells [16,34]. The increased formation of NO-metabolites in the respiratory tract in COPD can result from the effects of such factors as pathogenic bacteria and viruses, the inhalation of a range of exogenous compounds including cigarette smoke, nitrogen dioxide and fine particles [35][36][37]. Furthermore, it has been shown [38,39] that the increase in the amount of nitric oxide products is associated with increased hypoxia in patients with severe COPD.…”
mentioning
confidence: 99%